Impact of maternal weight on pregnancy outcomes: a systematic review. Issue 4 (11th July 2016) - Ayensu, Jessica; Annan, Reginald Adjetey; Edusei, Anthony; Badu, Eric
Abstract : Purpose: The nutritional status of a woman before and during pregnancy is important for a healthy pregnancy outcome. The increasing prevalence of maternal overweight and obesity worldwide has become a problem of concern among public health professionals. The purpose of this paper is to review the evidence regarding the impact of maternal weight on pregnancy outcomes to facilitate the provision of evidence-based information to pregnant women during antenatal clinics in Ghana. Design/methodology/approach: A search was conducted in PubMed, PLOS ONE, Cochrane, Embase and bibliographies for all studies on maternal weight and pregnancy outcomes published from January 2000 to May 2013. The key words used for the search were: "pre-pregnancy BMI", "gestational weight gain", "maternal weight", "pregnancy outcomes" and "birth outcomes". Findings: The search yielded 113 papers; out of these, 35 studies were included in the review after exclusion of duplicates and irrelevant papers. Excluded papers included animal studies and human studies that did not meet inclusion criteria. Research limitations/implications: The review only considered papers published from 2000 to 2013 and might have left out other important papers published before 2000 and after 2013. Practical implications: The origins of the studies included in the review suggest paucity of studies on maternal weight and pregnancy outcomes in developing countries where there is a double burden of malnutrition. There is the need for more studies to be initiated in this area. Social implications: Results of this review have revealed that the extremes of maternal weight prior to and during pregnancy increase the risk of maternal and fetal complications. Originality/value: This paper provides evidential information on the impact of maternal weight on pregnancy outcomes for counseling during antenatal clinics.